2017
DOI: 10.1089/lgbt.2017.0003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Antiretroviral Therapy Adherence Among Transgender Women Receiving HIV Medical Care in the United States

Abstract: Our findings suggest several ways to potentially improve ART adherence of TWLWH including tailoring efforts to address the needs of TWLWH under age 40, increasing access to health insurance coverage, addressing mental health morbidities, building skills to improve medication adherence self-efficacy, and simplifying ART regimens when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…A recent meta-analysis reported that 19.1% of transgender women worldwide are HIV-infected (Baral et al, 2013). While transgender women are estimated to have 48-times the odds of being infected with HIV compared to all adults (Baral et al, 2013), previous studies have reported low rates of HIV treatment engagement and poor health outcomes related to their HIV infection (Mizuno, Beer, Huang, & Frazier, 2017; Pitasi, Oraka, Clark, Town, & DiNenno, 2017; Santos et al, 2014; Wiewel, Torian, Merchant, Braunstein, & Shepard, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that 19.1% of transgender women worldwide are HIV-infected (Baral et al, 2013). While transgender women are estimated to have 48-times the odds of being infected with HIV compared to all adults (Baral et al, 2013), previous studies have reported low rates of HIV treatment engagement and poor health outcomes related to their HIV infection (Mizuno, Beer, Huang, & Frazier, 2017; Pitasi, Oraka, Clark, Town, & DiNenno, 2017; Santos et al, 2014; Wiewel, Torian, Merchant, Braunstein, & Shepard, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…22 Our findings that 66% of respondents taking ART took their meds all of the time is similar to rates found among other community samples of TGNC PLWH 12,18,20 and lower than nationally representative samples of TGNC PLWH engaged in HIV care. 3,15 The difference in community and nationally representative samples, highlighted again in this study by our findings, is important. One Significance was tested using t-tests with continuous variables, and chi-squared for categorical variables.…”
Section: Discussionmentioning
confidence: 67%
“…26,27 Other factors affecting adherence were related to social instability and included homelessness and ''alternative'' (not renting or owning a home) housing, sex work, and drug use in the past year, not being able to access care because of finances, and experiencing verbal harassment. Some of these factors such as compromised access to care 15 have been supported by existing adherence research with TGNC PLWH, and among PLWH overall, including homelessness, 28 sex work, 29 and drug use. 28,30 As with adherence, different measures across studies may account for variation in risk, although sociostructural vulnerability is a common theme.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations